Optimalisasi Profil Pelajar Pancasila Dengan Mengintegrasikan Steam dan Pemetaan Gaya Belajar di SMP 1 Mempura - Elni Yakub; Corrienna Abdul Talib; Mahmud Alpusari; Neni Hermita; Tri Umari; M. Arli Rusandi; Khairiyah Khadijah (PUCUK REBUNG: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The community service activity at SMP 1 Mempura, Siak District, Riau Province, is an initiative to integrate Pancasila values with the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in education. The collaboration between Universitas Riau and Universiti Teknologi Malaysia fostered educational innovation, focusing on identifying students' learning styles by guidance counselors. This activity targets the relevance of Pancasila in the digital era, the integration of STEAM with Pancasila, and understanding the variation in students' learning styles. The goals include enhancing teachers' understanding of learning style variations, optimizing guidance counselors' roles, and strengthening STEAM integration with Pancasila. Benefits include improved teacher insights in integrating STEAM and Pancasila and providing specific teaching strategies based on students' learning styles. The primary targets are guidance counselors, subject teachers, and students at SMP 1 Mempura. Methods used include brainstorming, training, and Q&A sessions. Results show SMP 1 Mempura's significant potential in STEAM education, with most students oriented towards a visual learning style. Future recommendations include expanding similar activities, enhancing teacher capacity in STEAM, and understanding learning styles.